A questão da formação psicanalítica na SPPA - Mabilde, Luiz Carlos (Revista de Psicanálise da SPPA, 2013)
O autor reflete sobre o ensino na SPPA e aprofunda o exame de sua formação psicanalítica. Propõe uma discussão aberta e dialética sobre aspectos evolutivos, conflitivos e ideológicos que caracterizam sua história. São estabelecidas três fases do seu desenvolvimento e fatos marcantes que as delimitaram. Por ultimo, o autor conclui ser a existência de duas correntes opostas de opinião – conservadora e progressista – a responsável por distintas formas de conceber/executar o ensino e seus inevitáveis conflitos. Ensino psicanalítico de psicanálise versus ensino de psicanálise, eis a questão! The question of psychoanalytic training at SPPA The author reflects on the education at SPPA and deepens the examination of his psychoanalytic training. He proposes an open and dialectical discussion about evolutionary, conflicting and ideological aspects, which characterize his history. Three phases of its development and milestones are established. Finally, the author concludes that the existence of two opposing currents of opinion – conservative and progressive – are responsible for different forms of understating and fulfilling the education and its inevitable conflicts. Psychoanalytic education of psychoanalysis versus education of psychoanalysis, this is the question!